1980
DOI: 10.1002/pssa.2210620132
|View full text |Cite
|
Sign up to set email alerts
|

XPS investigations of the interaction of oxygen with damaged (100) nickel surfaces

Abstract: The results of X‐ray photoemission spectroscopy investigations of the interaction of oxygen with damaged Ni (100) surfaces at 1100 K and of accelerated oxygen ions with Ni surfaces after argon ion bombardment of Ni (100) surfaces at room temperature are reported. The differences between these surface conditions as manifested in the O Is bands and the Ni 2p3/2 bands for different photoemission angles and the influence of the conditions of damage are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Also, there is a high binding energy peak (∼531.3 eV) that is 1.8 eV from the NiO O 1s peak, with a more pronounced degree of tailing. Previous reports have suggested that, at elevated temperatures, there is an evolution in oxide formation including transitions through nonstoichiometric states, which correlates with the evolution of a higher binding energy O 1s component shifted by ∼1.8 eV, attributed to Ni 2 O 3 defects. ,, The presence of Ni 2 O 3 is also confirmed in the Ni 2p spectrum, where the Ni 2p peak has the predominant third component near 855.3 eV. , Literature XPS results for Li + doped NiO, a complementary p-doped nickel oxide system, demonstrated a shift to lower binding energy (∼0.4 eV) in the O 1s spectrum as the concentration of Li + was increased . Changes in the Ni 2p line shape were also observed, with a decrease in the proposed NiO peak at ∼855 eV relative to the interstate peak at ∼856.7, although no direct correlations were discussed .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, there is a high binding energy peak (∼531.3 eV) that is 1.8 eV from the NiO O 1s peak, with a more pronounced degree of tailing. Previous reports have suggested that, at elevated temperatures, there is an evolution in oxide formation including transitions through nonstoichiometric states, which correlates with the evolution of a higher binding energy O 1s component shifted by ∼1.8 eV, attributed to Ni 2 O 3 defects. ,, The presence of Ni 2 O 3 is also confirmed in the Ni 2p spectrum, where the Ni 2p peak has the predominant third component near 855.3 eV. , Literature XPS results for Li + doped NiO, a complementary p-doped nickel oxide system, demonstrated a shift to lower binding energy (∼0.4 eV) in the O 1s spectrum as the concentration of Li + was increased . Changes in the Ni 2p line shape were also observed, with a decrease in the proposed NiO peak at ∼855 eV relative to the interstate peak at ∼856.7, although no direct correlations were discussed .…”
Section: Resultsmentioning
confidence: 79%
“…It is not anticipated that sufficient energy has been induced by annealing and the O 2 -plasma treatment to induce such a crystallographic reorganization. A Ni 2 O 3 layer also seems improbable since process temperatures in excess of 250 °C are required for dehydration/dehydroxylation and conversion to the higher order oxide. ,, Only by performing a detailed study with the rigorous standards given in Figure were we able to uniquely identify the presence of the oxy-hydroxide. The presence of NiOOH, a dipole species, and not Ni 2 O 3 , an artifact of p-doping, will have direct impact on understanding device performance, as discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…All X-ray photoelectron spectra were taken with an HP 5950 A ESCA spectrometer. Other details concerning ESCA system and energy calibration have been previously described (WAGNER et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…However, report of other depth also exists, Evans et al reported that a 18 A deep (about 9 ML) oxide layer forms at 300-370 K [28]. The onset of oxidation occurs at a coverage The oxide which forms is generally thought to be NiO, although there are also reports of NijOj [28,30] and NijO [31], which have not been discussed seriously in the literature. However, the epitaxial Hudson in their classic study [23], as well as Mitchell et al…”
mentioning
confidence: 99%